Leadership of China in the Innovative Development of the BRICS Countries - DOVGAL, Olena; GONCHARENKO, Nataliia; HONCHARENKO, Vladyslav; SHUBA, Tetiana; BABENKO, Vitalina (Journal of Advanced Research in Law and Economics, 2019)
The most important factor in the development of the modern economy is the intensification of international innovation activity. The degree of involvement in the international innovational market determines the overall level of competition of the country's economy. T he main objective of this research is a comparative analysis of the innovative development of the BRICS countries and the characterization of factors providing the leadership of China in it. The methodological basis of the article is the general scientific methods of scientific research: induction and deduction, comparative analysis and synthesis, generalization and realization of results, as well as index method.  In the study, the authors have proposed a method  for a comparative study of the innovative development of the BRICS countries, based on the calculation of cost-effectiveness indicators for various types of R&D (based on the results of patent activity and publication activity in the period 2006-2018), the determination of the integral index of the cost-effectiveness of R&D in individual member states and its comparisons with the ratings of the Global Competitiveness Index and the Global Innovation Index.  Based on the calculations, it was revealed that in China the integrated index of R&D cost effectiveness is the highest among the BRICS member states, which is confirmed by its highest results among the BRICS countries in the Global Competitiveness Index 4.0 2019 and in the Global Innovation Index 2019 and it testifies to high efficiency and prospects for further rapid development of the scientific and technological sphere in China. Based on the analysis of the features of China's innovative development, it is argued that the factors that ensure its leadership in the innovative development of the BRICS countries are the high efficiency of the chosen course of the country's innovative development, expressed in achieving high results with a minimum of resources expended, the availability of affordable and relatively cheap labor resources, and territorial diversification of the country, the presence of experience of innovative development of leading world powers accessible for studying and the formation and implementation of systematic governmental policy of innovative development. Based on the experience of China, the calculation of patent performance indicators and publication activity using the formula for calculating the cost-effectiveness index for research and development allows us to track the dynamics of the innovative development of a particular country based on the rapid development of the national scientific and technological sphere, rather than using innovative service accumulations from other countries.